Acting your age: on-line social interaction and the elderly - Dell, Peter; Marinova, Dora (Academic publishing houses and professional (Wydawnictwa Akademickie i Profesjonalne), 2008)
Self and identity are not only cornerstones of our well-being; they are practically the foundation of our existence. Socially constructed, they cannot develop in isolation. The chapter reports on a study which combined quantitative and qualitative methods to investigate the relationship between Internet use and identity, particularly age-identity, in older Internet users. It has a theoretical basis in symbolic interactionism ? particularly the theories of Erving Goffman ? and conceptualises identities as roles that are negotiated during social interaction.